'Pushed from above and pushed from below': Emotional labour and dual identities amongst senior probation officers in England and Wales. (April 2023) - Westaby, Chalen; Phillips, Jake; Ainslie, Sam; Fowler, Andrew
Senior Probation Officer's (SPOs) in England and Wales work at the 'front and centre' of the organisation's hierarchy. They act as both manager and developer of frontline probation practitioners. Previous research has focused on the emotional labour undertaken by probation practitioners yet there is very little research on the emotional labour of SPOs, even though they must be skilful emotion managers of their own emotions and those they supervise. Using data gathered from interviews with 28 SPOs and managers across England and Wales, we analyse how SPOs' emotions are 'controlled' by senior management, and how SPOs 'control' the emotions of frontline workers they supervise. SPOs attempts at managing emotions are resisted by their supervisees, and SPOs resist the emotional displays they are expected to present in their work role. We conclude by considering the impact of emotional labour on SPOs and how best to support them in their role.